2022
DOI: 10.1108/jmhtep-04-2021-0036
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 outbreak on the difficulties and burden experienced by family caregivers of older dependent persons

Abstract: Purpose The purpose of this paper is to identify the difficulties and overload/burden experienced by family caregivers of older dependent people during the COVID-19 outbreak. Design/methodology/approach A descriptive and cross-sectional study was conducted. This work was guided according to the Guideline strengthenin the reporting of observational studies in epidemiology (EQUATOR checklist). The study included 65 family caregivers of older people with physical or mental dependence. Caregivers were selected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 16 publications
2
14
2
Order By: Relevance
“…The change in the subjective burden, however, is rather small. This is in line with findings from Austria that there was no change in the objective burden (Rodrigues et al, 2021 ), and with studies from Australia, Portugal, the United States, Argentina, Canada, India, Italy, Japan, Taiwan, Germany and the United Kingdom, that report an increase in subjective burden (de Sousa et al, 2022 ; Hofstaetter et al, 2022 ; Lorenz‐Dant & Comas‐Herrera, 2021 ; Truskinovsky et al, 2022 ). Caregivers experienced not only negative effects, but also positive effects of the pandemic, such as the slower pace (Lightfoot et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The change in the subjective burden, however, is rather small. This is in line with findings from Austria that there was no change in the objective burden (Rodrigues et al, 2021 ), and with studies from Australia, Portugal, the United States, Argentina, Canada, India, Italy, Japan, Taiwan, Germany and the United Kingdom, that report an increase in subjective burden (de Sousa et al, 2022 ; Hofstaetter et al, 2022 ; Lorenz‐Dant & Comas‐Herrera, 2021 ; Truskinovsky et al, 2022 ). Caregivers experienced not only negative effects, but also positive effects of the pandemic, such as the slower pace (Lightfoot et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…We contribute to the literature by identifying which characteristics relate to changes in objective and subjective burden during the COVID‐19 pandemic. Prior research shows that during the pandemic informal caregivers experienced changes in responsibilities as well as in mental, physical and financial health (de Sousa et al, 2022 ; Greaney et al, 2020 ; Lorenz‐Dant & Comas‐Herrera, 2021 ). These consequences differed for caregivers with different characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have called for attention to the particularly negative impact of this pandemic on caregivers. Eurocarers and IRCCS-INRCA identified a significant impact on social relationships, quality of life, and physical or mental health [ 27 ], whereas Sousa et al reported a decrease in caregivers’ time and an increase in fatigue [ 43 ]. An additional burden was also mentioned in this regard, along with the need for support measures to assist carers in facing this problem [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last two and a half years, the COVID-19 pandemic has reached almost every part of society and affected people in different ways. It has affected people’s physical and mental health [ 1 , 2 , 3 , 4 , 5 ], but it is much more than a health crisis; it is a human, economic, and social crisis that, if not adequately addressed, can lead to an increase in inequality, exclusion, discrimination, and global unemployment [ 6 ].…”
Section: Introductionmentioning
confidence: 99%